Pengembangan Modul Ajar Kurikulum Merdeka Dalam Proses Pembelajaran Ppkn Sebagai Bentuk Pendalaman Materi UUD NRI 1945 di Kelas X SMAN 1 PamarayanPengembangan Modul Ajar Kurikulum Merdeka Dalam Proses Pembelajaran Ppkn Sebagai Bentuk Pendalaman Materi UUD - Ronni Juwandi; Listi Fitriani; Tamrohul Ikhsani; Muhammad Roji Firdaus; Enday Nurmahdiah (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This research aims to ensure accuracy, ease of use, and effectiveness in the learning module development process which aims to increase understanding of the content of the 1945 Constitution of the Republic of Indonesia (UUD 1945). In this research, research and development (R&D) methods are used using the ADDIE development model, namely analysis, design, development, implementation, and evaluation. In the research results, it is known that the results of expert validation of teaching materials obtained a score of 96% and validation of material experts obtained a score of 91%. In the practicality results obtained from the response questionnaire to teachers and students after using the teaching modules used, the practicality results for teachers were 94% and students were 98%. In the results of its effectiveness by giving evaluation questions to class X students, an average of 83.7 was obtained, while the KKM for class The results of this research show that the learning module that has been created meets the third evaluation standard, namely validity, ease of use, and effectiveness.